Komunikasi Empatik untuk Literasi Inklusif: Peningkatan Emotional Intelligence dan Teamwork Relawan Gerakan Suka Baca di Depok - Safira Hasna; Ruvira Arindita; Kussusanti; Wildan Faisol; Fayyaza Febriyanti; Angie Amalia (Aplikasia: Jurnal Aplikasi Ilmu-ilmu Agama, 2026)
Abstract - The low capacity for empathic communication and teamwork among volunteers of the Gerakan Suka Baca (GSB) Community in Depok has hindered the effectiveness of literacy mentoring for marginalized children. This community service activity aimed to enhance the emotional intelligence and teamwork skills of 20 GSB volunteers at Sekolah Master Depok. The program was implemented through interactive training grounded in Participatory Action Research (PAR) and experiential learning, employing methods including lectures, discussions, simulations, and field mentoring involving 20 volunteers. Evaluation was conducted through pre-test and post-test assessments. The results demonstrated significant improvements across all volunteer competency indicators: self-awareness increased from 38.1% to 87.6%, empathy from 57.1% to 91.4%, and team collaboration from 66.7% to 93.3%. Qualitatively, behavioral changes were observed among volunteers, reflecting more empathic, collaborative, and reflective communication practices in accompanying marginalized children. This program contributed to strengthening the internal capacity of other literacy communities. Program sustainability is ensured through the establishment of an internal volunteer trainer team (trainer of trainers) and the integration of an empathic communication module into the GSB new volunteer orientation curriculum.   Keyword: Communication, Empathic, Emotion, Collaboration, Volunteers.   Abstrak - Rendahnya kemampuan komunikasi empatik dan kerja sama tim relawan Komunitas Gerakan Suka Baca (GSB) di Depok menghambat efektivitas pendampingan literasi bagi anak-anak marjinal. Kegiatan pemberdayaan masyarakat ini bertujuan meningkatkan kecerdasan emosional dan kerja sama tim 20 relawan GSB di Sekolah Master Depok. Program dilaksanakan melalui pelatihan interaktif berbasis Participatory Action Research (PAR) dan experiential learning dengan metode ceramah, diskusi, simulasi, dan pendampingan di lapangan terhadap 20 relawan. Evaluasi dilakukan melalui pre-test dan post-test. Hasil kegiatan menunjukkan peningkatan signifikan pada seluruh indikator kemampuan relawan: self-awareness meningkat dari 38,1% menjadi 87,6%, empathy dari 57,1% menjadi 91,4% serta team collaboration dari 66,7% menjadi 93,3%. Secara kualitatif, terjadi perubahan perilaku relawan menuju komunikasi yang lebih empatik, kolaboratif, dan reflektif dalam mendampingi anak-anak marjinal. Program ini berkontribusi pada penguatan kapasitas internal komunitas literasi lainnya. Keberlanjutan program dijamin melalui pembentukan tim pelatih internal relawan (trainer of trainers) dan integrasi modul komunikasi empatik ke dalam kurikulum orientasi relawan baru GSB.   Kata kunci: Komunikasi, Empati, Emosi, Kolaborasi, Relawan.